Konsep Revolusi Kebudayaan Menurut Mao Zedong - Sri Harmini; Nusyirawan Nusyirawan (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
The purpose of this paper is to describe Mao Zedong's thoughts on especially his concept of cultural revolution. This study describes the cultural revolution which understanding as a societal strategy of change which being put foward by Mao according to Marx's concept of historical step toward communist society.Marx's and Lenin's concepts influence Mao's thoughts and policies during his power. As Lenin did to Marx, Mao took only the core of their thoughts and then modify its content to suit China's objective conditions. Mao's concept of cultural revolution is a long, thorough and continuous process that begins from one event leads to another.